Three-dimensional through-flow modelling of axial flow compressor rotating stall and surge - Righi, Mauro; Pachidis, Vassilios; Könözsy, László Z.; Pawsey, Lucas (Elsevier, 2018)
This paper presents a three-dimensional through-flow approach based on the cylindrical Euler equations incorporating a body force method. Blade performance is captured through a mixture of empirical correlations and a novel reverse flow treatment. The code is the first application of a physically correct Godunov solver to three-dimensional rotating stall and surge modelling. This solver ensures the accurate calculation of inter-cell fluxes unlike in typical modern CFD codes in which the non-linear convective terms are linearised. Validation consists of modelling a low speed three-stage axial compressor in all operating regions, recreating the reverse flow, rotating stall and forward flow characteristics with good agreement to experimental data. Additional comparisons are made against rotating stall cell size and speed, to which good agreement is also shown. The paper ends with some full surge cycle simulations modifying both the tank volume after the compressor and the level of inlet distortion applied. Both tank volume and level of distortion have been found to affect the type of instability developed. The development of this code is a step forward in compressor rotating stall and reverse flow modelling and allows recreation of a full compressor map at a significantly low computational cost when compared to commercially available 3D CFD codes.
Keywords: Post-stall modelling; Through-flow code; Rotating stall; Surge; Axial compressors; Godunov-type schemes